Report on the 17th Annual Land O'Lakes Bioanalytical Conference. (November 2016) - Burns, Erik C; Moran, Jeff; Breidinger, Sheila; Ho, Stacy; Guthrie, Randy; Amaravardi, Lakshmi
17th Annual Land O'Lakes Bioanalytical Conference, Madison, WI, USA, 11–14 July 2016 The 17th Annual Land O'Lakes Bioanalytical Conference, titled 'Biomarker Validation, Stability, and Regulatory Concerns', was held on 11–14 July 2016 (Monday through Thursday) in Madison, WI, USA. The Land O'Lakes Conference is presented each year by the Division of Pharmacy Professional Development within the School of Pharmacy at the University of Wisconsin–Madison (USA). The purpose of this 3-day conference is to provide an educational forum to discuss issues and applications associated with the analysis of xenobiotics, metabolites, biologics and biomarkers in biological matrices. The conference is designed to include and encourage an open exchange of scientific and methodological applications for bioanalysis. To increase the interactive nature of the conference, the program is a mixture of lectures, interactive discussions and a poster session. This report summarizes the presentations at the 17th Annual Conference.